Identifying barriers and disparities in the healthcare of patients with alopecia areata: a mixed-methods analysis using claims data and qualitative interview data - Matthias Augustin; Christine Blome; Katharina Müller; Kristina Hagenström; Toni Maria Janke; Beke Hester; Theresa Klinger; Brigitte Stephan (BMJ Open)
Objectives Alopecia areata (AA) is a chronic immune-related disease with non-scarring hair loss. Treatment may reduce disease activity but cannot cure. Even though AA can be very burdensome to patients, the German social act has categorised AA as a ‘lifestyle disease’ and treatment is not covered by statutory health insurances (SHI). We aimed to characterise the healthcare situation of patients with AA in Germany, including potential inequalities, and to derive recommendations for action.Design This mixed-methods study combined: (1) semistructured qualitative interviews with patients and dermatologists, analysed through qualitative content analysis and (2) claims data analyses of a large nationwide German SHI from 2016 to 2020. Both types of data were collected and analysed in parallel to enable integrated analysis. Consecutively, an expert panel derived recommendations for action.Setting Interviews were conducted online or via telephone.Participants Patients were recruited conveniently via a dermatological outpatient clinic, patient organisations and social media. Dermatologists were recruited from a nationwide network and the dermatological societies.Primary and secondary outcome measures Exploration of the healthcare situation of adult persons with AA in Germany, investigating potential barriers to adequate care and identifying potential inequalities of access to care.Results We interviewed 20 patients (mean age 40.7 years; 75.0% female) and 14 dermatologists (mean age 48.4 years, 50.0% female). SHI data included 4692 persons with AA in 2020 (prevalence 0.23%; mean age 55.8 years; 76.2% female). The lack of reimbursement was criticised by both patients and dermatologists. Though 57.5% of patients received at least one drug prescription, mostly topical therapies, access to approved systemic drugs was very low. Drugs were prescribed mostly by general practitioners (41.1%) and dermatologists (32.8%). Some patients were sceptical regarding the side effects of treatment and criticised exclusively symptomatic treatment. Patients reported an urge for information and exchange with others, as well as different ways of handling their disease, such as acceptance, and frustration or desperation. Patients living in urban areas received topical therapies more often than patients in rural areas. Furthermore, women were more likely to receive treatment than men. Recommendations for action include reimbursement of AA medication and developing a platform providing information on AA to physicians and patients.Conclusions The disease burden and frustration of patients with AA is high, mostly caused by limited treatment options and lack of reimbursement, limiting access to approved drugs such as Janus kinase inhibitors.Through the mixed-methods design, we were able to combine patient experiences and quantitative data reflecting the reality of healthcare in Germany.